2015
DOI: 10.3133/sir20155075
|View full text |Cite
|
Sign up to set email alerts
|

Median nitrate concentrations in groundwater in the New Jersey Highlands Region estimated using regression models and land-surface characteristics

Abstract: Geographic and environmental characteristics evaluated as possible explanatory variables in models of median nitrate concentrations in groundwater in the NJ Highlands Region (Appendix 2 available at http://dx.doi.org/10.3133/ sir20155075) v nondetects (left-censored data) in median nitrate-concentration calculations. Median concentrations also were determined using three alternative methods of handling nondetects. Treatment of the 23 percent of samples that were nondetects had little effect on estimated median… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Statistical methods have been used to study the relationship between groundwater nitrate contamination and predictor variables. For example, multivariate statistical methods like ordinary least square regression (OLS) have been applied in many studies to investigate the relationship between groundwater nitrate contamination and land use conditions [19][20][21]. However, OLS has a drawback of overfitting the data by regressing random error in the model rather than the relationship between the variables when there are numerous variables.…”
Section: Introductionmentioning
confidence: 99%
“…Statistical methods have been used to study the relationship between groundwater nitrate contamination and predictor variables. For example, multivariate statistical methods like ordinary least square regression (OLS) have been applied in many studies to investigate the relationship between groundwater nitrate contamination and land use conditions [19][20][21]. However, OLS has a drawback of overfitting the data by regressing random error in the model rather than the relationship between the variables when there are numerous variables.…”
Section: Introductionmentioning
confidence: 99%
“…Fischer et al (2004) described municipal and industrial discharges as point sources of nutrients (forms of nitrogen and phosphorus) in the Delaware River Basin and septic systems and the application of fertilizer in agricultural and urban as non‐point sources of nutrients. Baker et al (2015) reported that median nitrate concentrations in groundwater within the New Jersey Highlands Region, which overlaps much of the Highlands Province, were positively correlated with percentages of urban land, agriculture, and septic‐system density. Although elevated phosphorus, ammonia, and nitrite plus nitrate levels in Pinelands streams have been associated with direct sewage discharges (Fusillo, 1981; Schornick & Ram, 1978; Zampella, 1994), compared to the northern region, fewer point discharges are presently found in the Outer Coastal Plain streams.…”
Section: Discussionmentioning
confidence: 99%